Self-Esteem dan Social Comparison Perannya Terhadap Body Image Mahasiswi Sekretaris Sekolah Tinggi Ilmu Komunikasi dan Sekretari X - Rositha, Sherly Jaya; Rahayu, Anizar (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The purpose of this research is to determine the role of self-esteem and social comparison in relation to body image among female students of the School of Communication Science and Secretary X. This study is a quantitative research with a sample size of 152 female students. The sampling technique used a purposive non-probability sampling method. Data collection was done using Likert scale models, including a body image scale, self-esteem scale, and social comparison scale. Data analysis techniques involved Bivariate Correlation Analysis and Multivariate Correlation Analysis. The research results indicate that there is a significant role of self-esteem on body image with a correlation coefficient (R)= 0.657, (R2)= 0.431, Bx1y=0.934, and p= 0.000<0.05, demonstrating a positive relationship between self-esteem and body image among female students of the School of Communication Science and Secretary X. Additionally, there is a significant role of social comparison on body image with a correlation coefficient (R)=0.625, (R2)=0.390, Bx2y= 0.431, and p= 0.000<0.05, indicating a negative relationship between social comparison and body image among these students. Furthermore, there is a significant combined role of self-esteem and social comparison on body image with a correlation coefficient (R)= 0.724, (R2)= 0.524, and p= 0.000<0.05, showing a significant relationship between self-esteem, social comparison, and body image among female students of the School of Communication Science and Secretary X. The contribution of self-esteem to body image is 65.7%, while the contribution of social comparison to body image is 6.7%.